Criminal Liability for Fatal Traffic Negligence under Article 310(4) of Indonesian Road Traffic Law: A Juridical Analysis of Decision No. 75/Pid.Sus/2023/PN Mnd - Noviane Hewa Kelung; Linda Lidia Imon (Journal Social Civilecial, 2026)
Fatal traffic accidents caused by negligent driving remain a significant legal and social problem in Indonesia, particularly in cases involving intoxication and driver fatigue. This study aims to analyze the application of Indonesian positive law to fatal traffic negligence and evaluate the judicial reasoning in Decision No. 75/Pid.Sus/2023/PN Mnd of the Manado District Court. The research employed a normative juridical method using statute and case approaches. Primary legal materials consisted of the Indonesian Criminal Code, Law No. 22 of 2009 concerning Road Traffic and Transportation, and the relevant court decision, while secondary materials included legal doctrines, scholarly books, and journal articles related to criminal liability, negligence, and punishment. The findings show that Article 310 paragraph (4) of Law No. 22 of 2009 functions as lex specialis in relation to Article 359 of the Criminal Code because it specifically regulates negligent driving resulting in death within the context of road transportation. The court correctly established the legal elements of negligent driving causing death through evidence demonstrating that the defendant drove a motorcycle while intoxicated and severely fatigued, resulting in a fatal collision. However, the study also finds that the two-year imprisonment imposed by the court raises concerns regarding proportionality and victim-oriented justice because the punishment may not adequately reflect the seriousness of the defendant’s preventable risk-taking conduct and the irreversible loss suffered by the victim’s family. The study concludes that stronger sentencing consistency, clearer judicial reasoning, and broader integration between criminal sanctions and road-safety policies are necessary to improve traffic-law enforcement in Indonesia.